Academic Performance Mahasiswa: Pengaruh Work-Life Balance dan Academic Stress melalui Self-Efficacy - Dwi Pangestuti; Osly Usman (JURNAL RISET MANAJEMEN (JURMA), 2026)
This research explores the relationship between work-life balance, academic stress, and students’ academic performance by examining the mediating role of self-efficacy. The study is based on Social Cognitive Theory, which explains that self-efficacy plays an essential role in influencing individual behavior and achievement. A quantitative explanatory survey method was applied, involving undergraduate and postgraduate students from the Faculty of Economics, Universitas Negeri Jakarta, as research participants. Data collection was conducted using online questionnaires, while the analysis employed the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique. The results demonstrate that work-life balance is positively associated with academic performance, although the relationship is not statistically significant. Meanwhile, academic stress has a negative but insignificant effect on academic performance. The findings also show that work-life balance significantly enhances students’ self-efficacy, whereas academic stress significantly decreases self-efficacy levels. Furthermore, self-efficacy has a significant positive impact on students’ academic performance. However, the mediation test indicates that self-efficacy does not significantly mediate the relationship between work-life balance, academic stress, and academic performance. In general, the study underlines the importance of self-efficacy in supporting academic achievement among students. Therefore, universities are expected to promote programs focused on strengthening self-efficacy, improving stress management, and maintaining a healthy balance between academic responsibilities and personal life to support sustainable academic success.